Revolutions across borders : Jacksonian America and the Canadian Rebellion - Dagenais, Maxime, 1979-; Mauduit, Julien, 1979-; Greenberg, Amy S., 1968- (Rethinking Canada in the world, 2019)
"Starting in 1837, rebels in Upper and Lower Canada revolted against British rule. Their aim: reform a colonial government that they believed was unjust. While the Canadian Rebellion of 1837-38 is often studied as a small scale, localized event, Maxime Dagenais and Julien Mauduit's Revolutions across Borders: Jacksonian America and the Canadian Rebellion demonstrates that the crisis in Lower and Upper Canada was a major continental event, with dramatic transnational consequences. This ground-breaking study, with implications on both sides of the Canada-US border, analyses the extent of the Canadian Rebellion beyond British North America and into Jacksonian America. It also examines the ways the turbulent Jacksonian period influenced rebel leaders and the course of the Rebellion. Contributors explore the Rebellion's social and economic dimensions, how it had a significant impact on American politics and policy-making, and how important changes south of the border influenced this Canadian event. They show how malleable border/borderland relations were at the time, how it pushed Americans that had grown frustrated with the young republic to consider an "alternative republic" in Canada, how the rebels planned on establishing a new monetary system, how it played a major role in Martin Van Buren's defeat in 1840, and how America's changing economic alliances doomed the Canadian Rebellion before it even started. Revolution across Borders not only forces Canadians to reevaluate the transnational importance of this Canadian event, but it also obliges historians of early America to pay greater attention to Canada's impact on the young republic."--